An NAC domain transcription factor ATAF2 acts as transcriptional activator or repressor dependent on promoter context - Nagahage, Isura Sumeda Priyadarshana (Plant Biotechnol (Tokyo), 2018)
The ARABIDOPSIS THALIANA ACTIVATION FACTOR 2 (ATAF2) protein has been demonstrated to be involved in various biological processes including biotic stress responses, photo morphogenesis, and auxin catabolism. However, the transcriptional function of ATAF2 currently remains elusive. Therefore, to further understand the molecular function of ATAF2, we evaluated the transcriptional activities of ATAF2 using a transient assay system in this study. We used an effector consisting of a GAL4-DNA binding domain (GAL4-BD) fused to ATAF2, and observed upregulated reporter gene expression, suggesting that ATAF2 potentially has transcriptional activation activity. ATAF2 has been shown to activate reporter gene expression under the control of the ORE1 promoter. By contrast, ATAF2 significantly repressed reporter gene expression driven by the NIT2 promoter. These data suggest that ATAF2 is a bifunctional transcription factor that can alter target gene expression depending on the promoter sequences.